2003
DOI: 10.1079/bjn2003867
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of the integrity of rat caeco-colonic mucosa by resistant starch, but not by fructo-oligosaccharides, in dextran sulfate sodium-induced experimental colitis

Abstract: Butyrate is recognised as efficient in healing colonic inflammation, but cannot be used as a long-term treatment. Dietary fibre that produces a high-butyrate level when fermented represents a promising alternative. We hypothesised that different types of dietary fibre do not have the same efficiency of healing and that this could be correlated to their fermentation characteristics. We compared short-chain fructo-oligosaccharides (FOS) and type 3 resistant starch (RS) in a previously described dextran sulfate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(71 citation statements)
references
References 50 publications
(53 reference statements)
1
70
0
Order By: Relevance
“…The greater weight gain of conventional relative to germ- free rats has been explained previously in terms of energy harvest by the large-bowel microbiota (37). Although many studies have explored the health-promoting aspects of consuming RS and other nondigestible carbohydrates (4,24,27), the results from this report indicate that the effects on the host are extremely complex. We have shown that RS-induced alterations in microbiota composition resulted in elevated expression of Gsta2, which belongs to one of two supergene families that encode glutathione S-transferases.…”
Section: Discussionmentioning
confidence: 46%
“…The greater weight gain of conventional relative to germ- free rats has been explained previously in terms of energy harvest by the large-bowel microbiota (37). Although many studies have explored the health-promoting aspects of consuming RS and other nondigestible carbohydrates (4,24,27), the results from this report indicate that the effects on the host are extremely complex. We have shown that RS-induced alterations in microbiota composition resulted in elevated expression of Gsta2, which belongs to one of two supergene families that encode glutathione S-transferases.…”
Section: Discussionmentioning
confidence: 46%
“…This can bias experimental results, particularly in an immunological study. For instance, Umemoto et al 17) reported that fructo-oligosaccharide (FOS) suppressed colonic inflammation in a dextran sodium sulfate-induced colitis model using the Sprague-Dawley rat, while Moreau et al 18) reported the ineffectiveness of FOS in the same colitis model. Therefore, the construction of defined intestinal microflora is necessary, and the information should be available to researchers.…”
Section: Clostridiiformes (M59089)mentioning
confidence: 99%
“…Resistant starch also reduced DSS-induced colitis, whereas fructo-oligosaccharides did not show improvement. 74 A reduction of inflammation in the DSS model was also shown with goat milk oligosaccharides (GMO) as reported by Oligofructose and inulin (OFI) alone or 2 B. infantis strains (DSM 15158 and DSM 15159), isolated from infant feces, with and without OFI were fed to rats for 14 days in DSS-induced colitis. OFI alone or the B. infantis strains with and without OFI improved the DSS-induced acute colitis.…”
Section: Dss-induced Colitismentioning
confidence: 99%